Targeting Forkhead box O1-aquaporin 5 axis mitigates neuropathic pain in a CCI rat model through inhibiting astrocytic and microglial activation. Issue 4 (1st April 2022) - Yu, Yaoping; Wang, Meng; Yu, Xiao; Yan, Yi; Yu, Bo; Zhang, Dayin
ABSTRACT: Forkhead box O1 (FoxO1) is a critical molecule in modulating cell growth, differentiation and metabolism, acting as a vital transcription factor. This study explored the role of FoxO1 in chronic constriction injury (CCI)-induced neuropathic pain (NP). Microglial and astrocyte activation was achieved with lipopolysaccharide (LPS, 100 ng/mL) to establish an in-vitro NP model. Morphological alterations in LPS-induced microglia and astrocytes were assayed by light microscopy. The levels of inflammatory cytokines and proteins in microglia and astrocytes were gauged by enzyme-linked immunosorbent assay (ELISA), and Western blot (WB). The CCI-induced NP rat model was constructed for investigating the FoxO1-AQP5 axis in NP. LPS markedly expanded the expression of inflammatory factors and boosted the expression of FoxO1 and AQP5 in microglia and astrocytes. Inhibition of FoxO1 or AQP5 dramatically decreased the LPS-induced inflammation in microglia and astrocytes. In vivo, CCI exacerbated the inflammatory response and NP symptoms and substantially raised the contents of FoxO1 and AQP5 in rats' spinal cord tissues. Intrathecal administration of the Sirt1 agonist Resveratrol abated CCI-induced activation of FoxO1 and AQP5, abrogated CCI-induced mechanical hyperalgesia and thermal hyperalgesia, depressed microglial and astrocyte activation, and declined the generation of pro-inflammatory mediators in spinal cord tissues. Mechanistically, blocking the FoxO1-AQP5 pathway inactivated the ERK and p38 MAPK pathways. Suppressing the FoxO1-AQP5 axis alleviated CCI-induced NP and inflammatory responses by modulating the ERK and p38 MAPK signaling pathways. Graphical abstract: uf0001